Sadd Adz-Dzarâi’: Konsep dan Aplikasi Manajemen Pendidikan Islam - Muhlil Musolin (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to examine the concept of Sadd adz-Dzarâi and its implementation toward the concept of Islamic Education Management. This research would be beneficial to enrich scientific discussion on how to marry the concept of Islamic education management interact with Sadd adz-dzarâi, a concept in Ushul Fiqh. Using library research, this paper investigates ushul fiqh books and Islamic education management books to examine ushul fiqh’s concept and its implementation toward education management. This study found that the two concepts is compatible to certain extent as both concern on anticipating the possibility of losses in Islamic education institutions in the future.